Comparative Analysis of Metacognitive Reading Strategies of Freshmen Students - Veicel Joi Tejida; Jennelyn Lacar Raymundo (PT. Global Research Collaboration, 2025)
This study examined the metacognitive reading strategies employed by freshmen students at Patria Sable, Cagayan Valley Computer and Information Technology College, and the University of La Salette Incorporated. Specifically, it explored the most frequently used strategies and differences in strategy use based on students' profiles. A descriptive-comparative research design was utilized, incorporating the Metacognitive Reading Strategies Inventory and a reading test. The study included 176 respondents from Business Administration and Accountancy programs, with a majority preferring printed over digital reading materials. Findings indicated that Problem-Solving Strategies were the most frequently used, followed by Global Strategies and Support Strategies. However, overall metacognitive strategy use was inconsistent, suggesting limited awareness and self-regulation. While sex and reading material preference had minimal influence on strategy use, students' academic programs significantly affected their metacognitive engagement. Notably, Accountancy students demonstrated greater strategy use compared to Marketing Management students, highlighting possible curriculum-related differences. These findings underscore the need for targeted interventions to enhance students' metacognitive awareness and independence in reading.